Fighting against Corruption through Character Education: The Voices of Indonesian Primary School Teachers - MUHAMMAD SOFWAN; PANUT SETIONO; AHMED ELSAYED MOHAMED ELSAYED; FERDIAZ SAUDAGAR (Indonesian Research Journal in Education |IRJE|, 2018)
Indonesian government is currently through a tough moment where corruption has been massive. One of the long-term solutions of this practice is the implementation of character education from early ages. The purpose of this research was to find out the importance of character education in the fight against corruption for primary school students. The study was part of a research and development study aiming to design a model for integrating character education in integrated thematic learning in primary schools. We used semi-structure interviews to get data from eight participants who were Indonesian teachers of primary schools about the issue. This case study was analyzed through a thematic analysis. The findings show that character education is important for tackling corruption behaviors from early ages, shaping students’ mind towards the danger of corruption, producing excellent students with a good moral and behavior, and influencing teachers’ perception towards corruption. Recommendations are offered for Indonesian education betterment.